Get SMART: Improve Your Extension Objectives - David C. Diehl; Sebastian Galindo-Gonzalez (EDIS, 2012)
“SMART Objectives” assist educators and program planners in developing strong objectives that are Specific, Measurable, Achievable, Relevant and Time-bound. This 3-page fact sheet was written by David C. Diehl and Sebastian Galindo-Gonzalez, and published by the UF Department of Family, Youth and Community Sciences, June 2012.